Addressing Climate Change Challenges in Thailand’s Agricultural Economy - Pimpa, Nattavud (Journal of Ecohumanism, 2024)
Climate change is rapidly intensifying, leading to a surge in climate-related disasters worldwide. Thailand's agricultural sector, a cornerstone of its economy and food security, is particularly vulnerable to the adverse effects of these climatic shifts. This study delves into the multifaceted challenges faced by stakeholders in Thailand's agricultural sector, shedding light on the impact of climate change on their livelihoods and the broader food security landscape. Through in-depth interviews and thematic analysis, this research explores the experiences and perspectives of key stakeholders within the agricultural community. Participants consistently highlighted the disruptive influence of erratic rainfall patterns and rising temperatures on crop productivity and economic stability. These climate-induced challenges have exacerbated food shortages, compromised livelihoods, and heightened food insecurity. The study also underscores the critical importance of food security and the imperative to adopt resilient agricultural practices. To mitigate the impacts of climate change, it is essential to integrate climate change education into the Thai education system. This will equip future generations of farmers with the knowledge and skills necessary to adapt to changing climatic conditions and implement sustainable agricultural strategies.